Gaya Belajar Mahasiswa Pendidikan Matematika Universitas Flores dalam Pemahaman Konsep Fungsi - Vivien Restianim; Agnes Pendy; Juwita Merdja (SPEJ (Science and Physic Education Journal), 2020)
The purpose of this research is to find out the dominant learning style of students of Department of Mathematic Education University of Flores in understanding the function concept and also to find out the correlation between gender and learning style. Furthermore, to determine the effect of learning styles on the learning outcomes of function materials. This type of research is qualitative and quantitative research. The results of this research is the majority of students of of Department of Mathematic Education University of Flores have Social group learning styles with 43.21%. On the other hand, the majority of mathematics education students are women, but this does not affect the choice of learning styles. In this study, learning styles affect student learning outcomes on the understanding of the functions concept with an F count is 16.978 greater than F table = 3.96. Keyword: Learning style, Function, Gender, Learning outcome